THE IMPLEMENTATION OF THE FAMILY HOPE PROGRAM (PHK) IN BINJAI HULU DISTRICT, SINTANG REGENCY - Mathilda Sunta; Yulius Yohanes; Arifin (CV. Radja Publika, 2026)
This research aims to analyze and describe the implementation of the Family Hope Program (Program Keluarga Harapan or PKH) in Binjai Hulu District, Sintang Regency. The results indicate that Communication in the planning and decision-making process regarding the fuel subsidy reduction compensation program was conducted by the government using a